Pemenuhan Hak Difabel di UIN Sunan Kalijaga dan Universitas Atma Jaya Yogyakarta - Juwantara, Ridho Agung (PLD UIN Sunan Kalijaga, 2020)
This study aims to reveal efforts to fulfill the rights of people with disabilities at Sunan Kalijaga State Islamic University (UIN) and Atma Jaya University, Yogyakarta. Data collection was carried out by interview, observation, and document study. Interviews were conducted with university leaders, heads of service units, lecturers, and students with disabilities. The results showed that: 1) UIN Sunan Kalijaga has made accessible rules and policies, while Atma Jaya University has not had a real policy; 2) The physical facilities and infrastructure on both campuses are quite accessible. However, there is still a need to expand accessibility in all faculties; 3) Fulfillment of resources and behavior on both campuses can reduce environmental barriers typically faced by people with disabilities.[Penelitian ini bertujuan untuk mengungkap upaya pemenuhan hak difabel di Universitas Islam Negeri (UIN) Sunan Kalijaga dan Universitas Atma Jaya Yogyakarta. Pengumpulan data dilakukan dengan wawancara, observasi, dan studi dokumen. Data diperoleh dari para pimpinan kampus, kepala unit layanan, dosen, dan mahasiswa difabel. Hasil penelitian menunjukkan bahwa: 1) UIN Sunan Kalijaga sudah membuat aturan dan kebijakan yang aksesibel, sedangkan Universitas Atma Jaya belum mempunyai kebijakan yang nyata; 2) Sarana dan prasarana fisik di kedua kampus sudah cukup aksesibel, namun masih dibutuhkan perluasan dan pemerataan di semua fakultas; 3) Pemenuhan sumber daya dan perilaku di kedua kampus sudah dapat mereduksi hambatan lingkungan yang biasanya dihadapi oleh para difabel.]